An Analysis of Translation Strategies of Honorific Term in the Film â€œThe Boss Babyâ€ - Sari, Aisya Novita; Zamzani, Zamzani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
Translation helps the people to communicate and to transfer the information given by others. In translation language and meaning is the key of those communication and information. The culture of each language is different from another. Honorific is one of the cultures in language. The aims of the study is to examine the translation strategy of honorific term in the film The Boss Baby in its English to Indonesian translation and the use of the honorific. In this research, the researchers mainly used the qualitative research design in the strategy of descriptive. The subject of his research is honorific. Meanwhile, the data or object is the translation of subtitle of the film The Boss Baby. The method and technique in collecting data is observation specifically in noting technique and the technique for analyzing data is identity method. Research instrument is human instrument. Based on the findings, there are six types of translation strategies used. Those six types are literal translation, naturalization, generalization, reduction, transposition, and linguistic compression. The most used translation strategy is literal translation and the least one is transposition.